Editorial - Ally, Mohamed; Zhang, Weiyuan (Canadian Journal of Learning and Technology, 2022)
This special issue of the Canadian Journal of Learning Technology contains articles presented at the Rethinking Online Education in the Knowledge Society with Emerging Technology Symposium jointly hosted by Beijing Normal University, Athabasca University, and Chongqing Open University in November 2021. The symposium was organized by the Chongqing Open University, China.